PENTINGNYA IMUNISASI - Maimunah Maimunah (Universitas Negeri Medan, 2017)
Improvement of human quality in a country used internationally in the Millennium Development Goal's (MDG's).One of the MDG's goal is to reduce child mortality by two thirds. Based on Indonesian Demographic and Health Survey (IDHS) 2007, approximately 146,000 infants aged 0-1 years and 86,000 new borns (0-28 day extension Lalang village health center field. This research is a quasi experimental design with One - Group Pretest-Posttest and the total sample of 30 people. The instrument used in this study is to test the validity and reliability test. Methods of data analysis using the chi-square test with 95% degree of confidence. The results showed that prior to counseling ( pre-test) indicates knowledge of mothers gained a mean of 17.03, standard deviation of 7.69, and a standar error of 1.40 value. After counseling(Post-test) indicates knowledge of mothers gained a mean of23.50, standard deviation7.57, and the standard error value of 1.38. It is expected that this research can be used by nurse educators to develop appropriate teaching methods to improve students' ability in understanding how to make good health education so that students can apply them in the community.